Studies of curing cycle of carbon fiber/epoxy resins (8552® and M21®) prepregs based on thermal and rheological analyses - Silva, Sheila Marques; Silva, Carolina Paiva Nascimento; Silva, Thiago de Carvalho; Rezende, Mirabel Cerqueira; Botelho, Edson Cocchieri; Costa, Michelle Leali (Eclética Química, 2022)
Thermal and rheological characterizations were performed on prepreg produced with two different commercial epoxy resins - M21® and 8552® – aiming to study and optimize the curing cycle of structural components used in aerospace industry. Characterizations were performed by differential scanning calorimetry (DSC), rheology and dynamic mechanical analysis techniques were assessed and the results were correlated and supported by Fourier Transform Infrared spectroscopy. Additionally, to heating rates suggested by the material supplier, DSC analysis allowed to evaluate further heating rates: 2, 5, 10, 15 and 20 °C/min. Materials presented the n fractional order kinetic of cure and have in its formulation the presence of thermoplastics, in addition to epoxy and amine. Results confirmed that the best heating rates for processing both materials are the lower ones, as they result in a better control of the reactions between chemical compounds involved and the physical changes that are part of curing process stages. Results have analytically confirmed the suggested proposal for curing cycle from supplier is the best choice for materials involved.